Evaluación de los parámetros cinéticos de la transesterificación de los aceites vegetales. (2020)
In this work the transesterification reaction is studied, which occurs from of a vegetable oil and a short-chain alcohol in the presence of a catalyst to obtain biodiesel, through the analysis of different models kinetic parameters that allow us to find useful parameters to see how a series of reactions to certain operating conditions. A review of the literature that allowed to correlate the physicochemical properties of seven vegetable oils (corn, coconut, soybean, palm, palm kernel, babassu and jatropha), with the characteristics of fatty acid methyl esters, and therefore determine the kinetic models used with different types of catalysis, conditions and types of processes. Making use of experimental data, taken by Issariyakul and Dalai, an application was developed in MATLAB® using the fminsearch and fmincon functions to optimize and find the respective activation energies, rate constants and reaction orders.